The impact of diversity training in organizations: a systematic review using a meta-analysis methodology from 1991-2006 - Douglas, Bruce B., author; Gilley, Jerry, advisor (Colorado State University. Libraries, 2007)
The work environment in the United States (U.S.) has witnessed a dramatic change in the past decade. Because of this dramatic demographic shift, diversity initiatives have become necessary in organizations, mainly diversity training. While diversity training has become very popular in business and industry, its impact on employees has not kept pace. Therefore, the purpose of this research synthesis is to gather, summarize, and integrate past research since 1991 examining to effectiveness of diversity training in organizations. This review will be conducted with the intention of providing a clear and accessible synthesis of existing research to inform decisions makers of the effectiveness of diversity training in organizations. Articles were identified through computer database searching and hand searching of selected journals, from 1991 through 2006. Of the 166 studies reviewed at the second-level screening, only eight studies met the criteria for inclusion. Seven studies provided analyses on multiple outcomes. Six studies provided correlations, one study provided odds ratios, and one study provided Cohen's d effect sizes. Effect size estimates, tests for homogeneity of variance, and tests for publication bias were calculated using the Comprehensive Meta-Analysis, Version 2.0. The results of this meta-analysis indicate that diversity training has an effect on changing attitudes and behaviors in organizations. However, attitude and behavioral changes produced by diversity training are susceptible to impermanence if the environment and culture of the organization do not endorse and facilitate its longevity.
Keywords: diversity training; meta-analysis; organizations